Life in a Japanese American internment camp - Yancey, Diane (San Diego, CA : Lucent Books, 1998)
Discusses the course of Japanese immigration into the United States, events leading to the relocation of Japanese Americans during World War II, and the conditions they faced in the internment camps.
Includes bibliographical references (p. 99-105) and index.
Keywords: Japanese Americans -- Forced removal and internment, 1942-1945.; World War, 1939-1945 -- Concentration camps -- United States; World War, 1939-1945 -- Personal narratives, American